H. pylori infection and gastric cancer in Bangladesh: a case-control study. - Sarker, KK; Kabir, MJ; Bhuyian, AKMMU; Alam, MS; Chowdhury, FR; Ahad, MA; Rahman, MA; Rahman, MM (IJS Publishing Group, 2017)
Like that of other Asian countries gastric cancer (GC) is also a leading cancer in Bangladesh and also a cause for cancer-related mortality. Infection with Helicobacter pylori (H. pylori) is the strongest recognized risk factor for gastric adenocarcinoma. The infection is also prevalent in common people. This case-control study was carried out to find an association between GC and H. pylori infection in the community.To evaluate association of H. pylori and carcinoma of stomach this study was conducted at National Institute of Cancer Research & Hospital, Dhaka from January 2013 to December 2014. H. pylori status was determined serologically by using H. pylori kit in the department of Biochemistry laboratory of Bangabandhu Sheikh Mujib Medical University. In total, 114 patients with GC and 520 patients not having GC were studied as controls. Logistic regression method was used to calculate the odds ratio.Significantly more patients in the case group (86.8%) were found to be seropositive for H. pylori antigen in contrast to the control group (67.5%). All of the cases in the present study were in advanced stage. No significant association between H. pylori seropositivity and tumor location was found. It was noted that undifferentiated gastric carcinoma had slightly more association with H. pylori infection. Younger H. pylori-infected patients had been found to be at higher relative risk for GC than older patients.As there is a strong association found between GC and H. pylori infection special emphasis to eradicate H. pylori infection might reduce the incidence of this dreadly disease.